2021
DOI: 10.1371/journal.pone.0261685
|View full text |Cite
|
Sign up to set email alerts
|

Where is emotional feeling felt in the body? An integrative review

Abstract: Contemporary research on “embodied emotion” emphasizes the role of the body in emotional feeling. The evidence base on interoception, arguably the most prominent strand of embodied emotion research, places emphasis on the cardiac, respiratory and gastrointestinal systems. In turn, interoception has evidence-based links with improved emotion regulation. Despite the focus on separate bodily systems, it is unclear whether particular interoceptive locations play a greater role in emotional feeling and emotion regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 147 publications
0
12
0
Order By: Relevance
“…Our research emphasizes the crucial role of the AI in age‐related cognitive functions, particularly emotional reactivity. Previous research has suggested that IS serves as a physiological basis for emotional processes, has a significant positive correlation with emotional reactions (MacCormack et al, 2020), and diminishes with age (Davey et al, 2021; Dunn et al, 2010; Lautenbacher et al, 2017; Schandry, 1981). Our study builds upon this foundation by revealing a concurrent decrease in emotional reactivity with age.…”
Section: Discussionmentioning
confidence: 99%
“…Our research emphasizes the crucial role of the AI in age‐related cognitive functions, particularly emotional reactivity. Previous research has suggested that IS serves as a physiological basis for emotional processes, has a significant positive correlation with emotional reactions (MacCormack et al, 2020), and diminishes with age (Davey et al, 2021; Dunn et al, 2010; Lautenbacher et al, 2017; Schandry, 1981). Our study builds upon this foundation by revealing a concurrent decrease in emotional reactivity with age.…”
Section: Discussionmentioning
confidence: 99%
“…Other research focusing on the throat/neck region conducted has being conducted by our group but was halted due to Covid-19 pandemic. As the review by Davey et al (2021) points out, this is one of the three regions (along with the head and chest) that appears to be consistently associated with increased perceived activity across all emotions. Although in the current study the head/face and the chest were the most mentioned, these areas have already been explored extensively.…”
Section: Emotionsmentioning
confidence: 98%
“…Finally, it should be noted that while this manuscript was being finalized, an integrative review was published by Davey, Halberstadt & Bell (2021) that emphasizes the importance of observing the first sensation of the emotion in the body in relation to dealing with emotions, as discussed above. The authors also propose a methodology similar to ours.…”
Section: Emotionsmentioning
confidence: 99%
“…There are several common methods of measuring physiological activity, with the three most common being the heart, the skin, and the eyes/face/head, though this differs across areas of research (Davey et al, 2021;Moon et al, 2021). The current study specifically includes measures of Heart Rate (HR), Raw Electrocardiogram (ECG) activity, Galvanic Skin Conductance (GSR), Skin Temperature (SKT) and Chest Expansion as measures of internal ANS activity.…”
Section: Physiological Measures Of Embodied Emotionmentioning
confidence: 99%
“…Two reviews looking at measures of embodied emotion by Davey et al (2021) and Moon et al (2021) do not include movements as a measure of embodied emotion. Other previous research contests this as a person's movements can be used as a measure of emotion because people move differently depending on the emotion they are feeling (Behnke et al, 2021).…”
Section: Emotion and Motionmentioning
confidence: 99%